SEMIOTIC ANALYSIS OF IDIOMATIC IN THE MAZE RUNNER: THE DEATH CURE MOVIE - Anisa Alawiyyah; Ria Saparianingsih; Nadia Nurul Maulidiyah (Dialectical Literature and Educational Journal, 2021)
This research discussed the semiotic analysis of idiomatic expressions found in The Maze Runner: The Death Cure movie by Wess Ball and its impact on English. This research aimed to find idiomatic expressions revealed in the dialogue in the movie; to find the meaning of symbols contained idiomatic expressions in dialogues; to find the impact of semiotic analysis in idiomatic expressions found in movie. In this research, researchers used qualitative research in the type of content analysis using descriptive approach to help the analysis of the data that found in the movie. The researchers looked for idiomatic expressions in the movie and symbols of idiomatic expressions. Finally, researchers reveal the impact of semiotic analysis in idioms found in movie on English. From the results, there are 59 idiom expressions divided into lexemic and sememic idioms. From lexemic idiom found 37 phrasal verbs; 2 irreversible binomials; 10 phrasal compounds; and 1 incorporating verb. From the sememic idiom found 2 idioms of politeness; 1 idiom of detachment; 4 idioms of greeting; and 2 famous quotations idioms. There are 26 symbols from 59 idiom expression in the movie. Its effects on English make students more fluent in English and look like native speakers, add new vocabulary, make students aware of cultural differences in language, and know more about meaning.